2022
DOI: 10.21203/rs.3.rs-1777444/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of essential genes and drug discovery in bladder cancer and inflammatory bowel disease via text mining and bioinformatics analysis

Abstract: Background: Bladder cancer (BCa) is the most common malignancy of the urinary system. Inflammation is critical in the occurrence and development of BCa. The purpose of this study was to identify key genes and pathways of inflammatory bowel disease in BCa through text mining technology and bioinformatics technology, and to explore potential therapeutic drugs for BCa.Methods: Genes associated with BCa and Crohn's disease (CD) were detected using the text mining tool GenClip3, and analyzed using Gene Ontology (GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Population-based cohort studies suggested that IBD especial CD increases the risk of kidney cancer [11,12] . The risk of bladder cancer was only mildly elevated in patients with CD [12] , but some researchers found potential key genes involved in CD with bladder cancer [13] . IBD has been demonstrated as a risk factor for prostate cancer [14][15][16] , and preneoplastic changes have been observed in a mouse model of chemically-induced intestinal in ammation [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Population-based cohort studies suggested that IBD especial CD increases the risk of kidney cancer [11,12] . The risk of bladder cancer was only mildly elevated in patients with CD [12] , but some researchers found potential key genes involved in CD with bladder cancer [13] . IBD has been demonstrated as a risk factor for prostate cancer [14][15][16] , and preneoplastic changes have been observed in a mouse model of chemically-induced intestinal in ammation [17] .…”
Section: Introductionmentioning
confidence: 99%